Endocrine therapies in breast cancer - Buzdar, Aman U. (Oxford University Press, 2007)
Breast cancer is one of the leading causes of cancer mortality in women worldwide, and the risk of disease recurrence continues despite improvements in screening and treatment. For patients with hormone receptor-positive breast cancer, some form of endocrine therapy is central to the management of their disease. Tamoxifen has long been the mainstay of endocrine therapy in this group of patients. However, there is mounting evidence showing that the aromatase inhibitors are able to reduce overall oestrogen levels and appear to be better tolerated over a long term than tamoxifen. New and emerging indications for the aromatase inhibitors are providing clinicans (and patients) with alternative treatment options with differing side effect profiles. Part of the Oxford Oncology Library, this pocketbook will summarise the latest evidence-based and practical information on the use of endrocrine therapies in the management of breast cancer (early stage, metastatic disease, and prevention of disease). With contributions from leading oncologists from the MD Anderson Cancer Center, the book covers the range of endocrine therapies currently available to clinicians including ovarian ablation, anti-estrogens, aromatase inhibitors, fulvestrant, progestins, androgens, and combination endocrine and chemotherapy. The book also includes useful chapters on the identification and optimal selection of patients for endocrine therapy as well as the role of endocrine treatments in the prevention of breast cancer. This book will serve as an invaluable reference for all health care professionals involved in the management of patients with breast cancer